Executive Functions, Pragmatic Skills, and Mental Health in Children With Congenital Cytomegalovirus (CMV) Infection With Cochlear Implants: A Pilot Study - Löfkvist, Ulrika; Anmyr, Lena; Henricson, Cecilia; Karltorp, Eva (Frontiers in Psychology, 2020)
Congenital cytomegalovirus (cCMV) infection is the most common cause of progressive hearing impairment. In our previous study around 90 % of children with cCMV infection and CI had severely damaged balance function (Karltorp et al., 2014). Around 20 % had vision impairment, 15 % were diagnosed with Autism-Spectrum-Disorder and 20 % with ADHD. One clinical observation was that children with cCMV infection had problems with executive functioning (EF) while controls with genetic cause of deafness (Connexin 26 mutations; Cx26) did not have similar difficulties. Therefore, a follow-up study was initiated with the main objective to examine EF and pragmatic skills, in relation to mental health in children with cCMV infection, and compared to matched controls with Cx26 mutations (age, sex, hearing, non-verbal cognitive ability, vocabulary, socioeconomic status level). Ten children with cCMV infection and CI (4.8-12:9 years) and seven children with CI (4:8-12:8 years) participated in the study which had a multidisciplinary approach. Executive functioning was assessed both with formal tests targeting working memory and attention, parent and teacher questionnaires, and a systematic observation by a blinded psychologist during one test situation. Pragmatics and mental health was investigated with parent and teacher reports. In addition, early language outcome was considered in non-parametric correlation analyses examining the possible relationships between later EF skills, pragmatics, mental health. Children with cCMV had statistically significant worse pragmatic outcome and phonological working memory than controls, despite similar non-verbal cognitive ability and vocabulary. However, there were no statistical differences between groups on EF skills in everyday settings and mental health. There were associations between early language outcome and later EF skills, and pragmatics in the whole sample. Conclusion: Children with cCMV infection are at risk of developing learning difficulties in school due to difficulties with phonological working memory and pragmatic skills in social interactions.